Global trends in relative and absolute wealth concentrations (2014)
This paper compares changes in relative and absolute wealth concentrations to establish if both processes have followed similar trajectories. The findings indicate that while the level of relative wealth concentration has increased recently, it is not extraordinarily high in an historical perspective. On the contrary, the level of absolute wealth concentration is most likely higher than that previously occurred because of the increase in the wealth holdings and population size of high net worth individuals. The sustainability of this on-going absolute concentration of wealth is questionable insofar as the resulting pressure of investor demand for safe securities poses a potential threat for financial stability.